Nanostructure Engineering by Simple Tuning of Lipid Combinations. (19th February 2020) - Saw, Phei Er; Xu, Xiaoding; Zhang, Meng; Cao, Shuwen; Farokhzad, Omid C.; Wu, Jun
Abstract: Structural morphology is the key parameter for efficacy of nanomedicine. To date, lipid‐based nanomaterial has been the most widely used material in nanomedicine and many other biomedical applications. However, to the best of our knowledge, there has not been an in‐depth or systematic investigation of the structure–function relationship of lipid‐based nanostructures. In this report, we investigated the formulation of novel lipid‐based nanostructures via simple tuning of lipid combinations. To prove this concept, we used a combination of various ratios of simple and common phospholipids with different chain lengths (14‐carbon chain DMPC: 6‐carbon chain DHPC) to find out whether a myriad of novel lipid nanostructures could be obtained. Interestingly, many combinations resulted in distinct lipid nanostructures. Drug encapsulation tests confirmed that they are able to load large amounts of drugs for biological application. In vivo anti‐tumor efficacy revealed that certain lipid nanostructures possessed superior tumor retardation effects. Abstract : Einfaches Kombinieren von DMPC und DHPC führte zu vielfältigen Lipid‐Nanostrukturen mit charakteristischen Struktur‐Funktions‐Beziehungen, die sich bezüglich Zellaufnahme, Effizienz der Wirkstoffverkapselung und Antitumorwirkung in vivo unterscheiden.